Autosomal recessive posterior column ataxia with retinitis pigmentosa caused by novel mutations in the FLVCR1 gene. (2nd January 2015) - Shaibani, Aziz; Wong, Lee-Jun; Wei Zhang, Victor; Lewis, Richard Alan; Shinawi, Marwan
<x xml:space="preserve">Abstract</x> Posterior column ataxia with retinitis pigmentosa (PCARP) is an autosomal recessive disorder characterized by severe sensory ataxia, muscle weakness and atrophy, and progressive pigmentary retinopathy. Recently, mutations in the FLVCR1 gene were described in four families with this condition. We investigated the molecular basis and studied the phenotype of PCARP in a new family. The proband is a 33-year-old woman presented with sensory polyneuropathy and retinitis pigmentosa (RP). The constellation of clinical findings with normal metabolic and genetic evaluation, including mitochondrial DNA (mtDNA) analysis and normal levels of phytanic acid and vitamin E, prompted us to seek other causes of our patient's condition. Sequencing of FLVCR1 in the proband and targeted mutation testing in her two affected siblings revealed two novel variants, c.1547G>A (p.R516Q) and c.1593+5_+8delGTAA predicted, respectively, to be highly conserved throughout evolution and affecting the normal splicing, therefore, deleterious. This study supports the pathogenic role of FLVCR1 in PCARP and expands the molecular and clinical spectra of PCARP. We show for the first time that nontransmembrane domain (TMD) mutations in the FLVCR1 can cause PCARP, suggesting different mechanisms for pathogenicity. Our clinical data reveal that impaired sensation can be part of the phenotypic spectrum of PCARP. This study along with previously reported cases suggests that targeted sequencing of the FLVCR1 gene should be considered in patients with severe sensory ataxia, RP, and peripheral sensory neuropathy.